Reviewing National Sanitation to Reach Sustainable Development Goals - Gibson, Jim; Eales, Kathy; Nsubuga-Mugga, Chris (World Bank, Washington, DC, 2018)
The government of Uganda has given strong emphasis to eradicating open defecation and to encouraging people to invest in safe containment systems. Funding to local governments is spurring sanitation improvement on a significant scale. But as the pace of urbanization picks up in the country and the scale and density of urban settlements rise, local authorities and the ministries that support and service these areas will need to give greater attention to safe management of wastes beyond the on-site facilities of individual users. The SDGs shift the sanitation sector’s targets beyond a measurement of how many people have access to an adequate toilet and define outcomes in terms of safe management of human wastes across the whole service chain. It is only by understanding and managing the processes associated with each component in the chain, and ensuring they link and align with the preceding and subsequent components, that one can begin to define strategic interventions to improve the performance of the system. Developing insight into the nature of these processes and related activities will help to clarify the responsibilities, functions, and possibility for intervention by the various role-players and ministries in the sector as they strive for the realization of the objectives defined by the Sustainable Development Goals